Validation of analytical methods for heterocyclic amines in seven food matrices using high-performance liquid chromatography-tandem mass spectrometry. Issue 3 (3rd March 2020) - Lee, Youngsun; Hwang, Inju; Kim, Haesol; Youn, Hyeock; Kim, Cho-Il; Lee, Jee-Yeon; Park, Hyun-Mee
ABSTRACT: Heterocyclic amines (HCAs) are potent mutagens generated by the high temperatures of the cooking process. The purpose of this study was to develop and validate analytical methods for HCAs determination using high-performance liquid chromatography-tandem mass spectrometry in seven food matrices: corn oil, milk, 20% ethanol, pork, flat fish, sea mustard ( Undaria pinnatifida ), and radish. Six isotopically labelled internal standards were used for quantitation, and Chem Elut and Oasis hydrphilic-liphophilic balance cartridges were applied for sample preparation to remove interferences. Calibration curves showed good linearity ( R 2 > 0.99) in all matrices. The ranges of the method detection limit and method quantitation limit were 0.009–2.35 ng g −1 and 0.025–7.13 ng g −1, respectively. The recoveries ranged from 67.5% to 119.6%. The coefficients of variation ranged from 0.3% to 15.1% for intra-day and ranged from 0.8% to 19.1% for inter-day. The methods were applied to 24 total diet study samples for HCAs quantitation. These results indicate that the established methods are reliable for determining HCAs in various foods.